The base of party political support in Ireland: An update - David Madden (University College Dublin, UCD Centre for Economic Research, 2019)
A recent paper by Madden used concentration indices to examine the bases of party support in Ireland in the 2011 election. This note updates this work to incorporate the 2016 election using the latest wave of ESS data. The results show that in terms of the bases of party supports many of the features of the "earthquake election" of 2011 remain, in particular the widely differing support bases for Fine Gael and Sinn Fein. Concentration indices with respect to income show little change from the 2011 election. However, there is some evidence that the support base for Fianna Fail in 2016 was older and less well-educated than in 2011, with the change in support base for Fine Gael over the same period a mirror image.
Keywords: 330; Party support; social base; concentration index